The association between temperature variability, morbidity and mortality for specific categories of disease: A systematic review and meta-analysis - Maxwell D. Weidmann (Hygiene and Environmental Health Advances)
While research into temperature-related health outcomes has focused on absolute temperature exposure, an increasing number of studies have explored the distinct effect of temperature variability (TV). However, systematic reviews in this area have focused on a limited number of health outcomes and intra-day TV. A systematic review was therefore conducted for studies of intra- and/or inter-day TV and cardiovascular, respiratory, renal or mental illnesses through April 2023 (n = 38). There was a consistent relationship between cardiovascular disease (CVD) or respiratory disease (RD) morbidity, mortality and both diurnal temperature range (DTR) or short-term inter-day TV, particularly for the elderly. The effect of DTR and short-term inter-day TV were stronger on hot days and the warm season for CVD, but on cold days and cold season for RD. Meta-analysis for CVD or RD and DTR showed a significant 0.7 %/C° increase in CVD mortality, but not morbidity, while RD showed a significant 1.0 %/C° and 0.7 %/C° increase in morbidity and mortality, respectively. Most studies focused on CVD, RD, DTR or short-term inter-day TV, while few studies explored renal, GU, or mental health outcomes aside from schizophrenia. Future studies are needed to assess non-linear relationships between TV and disease, and the modifying effect of socioeconomic status.